2020
DOI: 10.1021/acsabm.0c00203
|View full text |Cite
|
Sign up to set email alerts
|

Non-leaching, Highly Biocompatible Nanocellulose Surfaces That Efficiently Resist Fouling by Bacteria in an Artificial Dermis Model

Abstract: Bacterial biofilm infections incur massive costs on healthcare systems worldwide. Particularly worrisome are the infections associated with pressure ulcers and prosthetic, plastic, and reconstructive surgeries, where staphylococci are the major biofilm-forming pathogens. Non-leaching antimicrobial surfaces offer great promise for the design of bioactive coatings to be used in medical devices. However, the vast majority are cationic, which brings about undesirable toxicity. To circumvent this issue, we have dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
(123 reference statements)
1
6
0
Order By: Relevance
“…Lastly, DDC − can be degraded to diethylamine and carbon sulfide in the presence of blood, due to the presence of plasma proteins and may therefore not be available to form the Cu(DDC) 2 complex [ 51 ]. Similar effects of the microenvironmental conditions in the artificial dermis model on the antibiofilm activity of antimicrobial agents were reported [ 42 , 48 , 52 ]. For example, Grassi et al [ 48 ] observed inferior biofilm inhibition by antimicrobial peptides in the artificial dermis model compared to a 3D lung epithelial model due to the presence of blood and proposed the development of nanocarriers as drug delivery vehicle [ 53 ].…”
Section: Resultssupporting
confidence: 73%
“…Lastly, DDC − can be degraded to diethylamine and carbon sulfide in the presence of blood, due to the presence of plasma proteins and may therefore not be available to form the Cu(DDC) 2 complex [ 51 ]. Similar effects of the microenvironmental conditions in the artificial dermis model on the antibiofilm activity of antimicrobial agents were reported [ 42 , 48 , 52 ]. For example, Grassi et al [ 48 ] observed inferior biofilm inhibition by antimicrobial peptides in the artificial dermis model compared to a 3D lung epithelial model due to the presence of blood and proposed the development of nanocarriers as drug delivery vehicle [ 53 ].…”
Section: Resultssupporting
confidence: 73%
“…When H 2 O 2 interacts with AcOH, it leads to the in situ formation of peracetic acid (AcOOH). AcOOH has 21.10% of active oxygen atoms and 1.81 oxidizing power. , Thus, the reaction between the AcOOH and sulfur compounds has been very effective in the EODS process and converts sulfurous organic compounds to sulfone. Also, benzoic acid loses protons and resonates because it is a stronger acid.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of CNMs with bacteria and viruses has also been under research for the development of new antimicrobial materials. Different surface modification and functionalization strategies of CNMs have been proposed to achieve materials with excellent antimicrobial properties and membrane filters against microbes. …”
Section: Cellulose Nanomaterialsmentioning
confidence: 99%